2005
DOI: 10.1590/s0021-75572005000600014
|View full text |Cite
|
Sign up to set email alerts
|

Bronquiolite aguda por rinovírus em lactentes jovens

Abstract: Objective: To determine the prevalence of rhinovirus infection in hospitalized young infants with acute bronchiolitis.Methods: Hospitalized children with acute bronchiolitis admitted to the Hospital São Lucas/PUCRS between May and September 2002 were selected prospectively. Nasopharyngeal samples were assayed for respiratory syncytial virus, parainfluenza, influenza and adenovirus by immunofluorescence. For rhinovirus test a reverse transcriptionpolymerase chain reaction for picornavirus was used, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
0
3
0
6
Order By: Relevance
“…After the screening by full text process, 136 studies were included for data extraction. During the data extraction process, 62 studies were excluded, leaving 74 for analyses (Figure ). Most studies were performed in pediatric populations from Brazil, Argentina, Chile, Mexico, and Uruguay.…”
Section: Resultsmentioning
confidence: 99%
“…After the screening by full text process, 136 studies were included for data extraction. During the data extraction process, 62 studies were excluded, leaving 74 for analyses (Figure ). Most studies were performed in pediatric populations from Brazil, Argentina, Chile, Mexico, and Uruguay.…”
Section: Resultsmentioning
confidence: 99%
“…In the South Brazilian region, the RV was detected in 17% of samples from infants younger than six months old hospitalized due to acute bronchiolitis. 16 …”
Section: Discussionmentioning
confidence: 99%
“…RVs were shown to have the capacity to infect the lower respiratory tract and to replicate effectively in lower airway cells even at core temperatures of 37uC, although greater viral yields are obtained at lower temperatures [80][81][82][83]. In line with these findings, studies using sensitive molecular viral detection methods have shown that RVs are a common cause of LRTI in infants and young children; including wheezing disorders, bronchiolitis, and pneumonia with potential subsequent hospitalisations [65][66][67][84][85][86][87][88][89][90][91][92]. Both prevalence and severity of LRTI induced by RVs are further increased in high-risk groups, especially in infants and young children with underlying chronic lung disease, such as those with bronchopulmonary dysplasia [93,94], asthma [66,90,95,96] and cystic fibrosis [97][98][99][100][101].…”
Section: Clinical Features Of Rv Infectionsmentioning
confidence: 99%